## Express the given function h as a composition of two functions f and g so that h (x )equals (f circle g )(x )commah(x)=(f◦g)(x), where one o

Question

Express the given function h as a composition of two functions f and g so that h (x )equals (f circle g )(x )commah(x)=(f◦g)(x), where one of the functions is 4 x minus 3.4x−3. h (x )equals (4 x minus 3 )Superscript 8h(x)=(4x−3)8 f (x )f(x)equals=4 x minus 3

in progress
0

Math
4 weeks
2021-12-28T22:30:46+00:00
2021-12-28T22:30:46+00:00 1 Answer
0 views
0
## Answers ( )

Answer:h(x) = g o f(x), with f(x) = 4x-3 and g(x) = x⁸

Step-by-step explanation:f(x) = 4x-3

h(x) = (4x-3)⁸

Note that what we do with f to obtain h is power the expression 4x-3 given by f 8 times, thus what we are composing f with a function g that takes a value and power it by 8, as a consecuence g(x) = x⁸, and

h(x) = g o f(x), with f(x) = 4x-3 and g(x) = x⁸.